Statical and Biological Investigation of Sturgeon Fish in Southern Part of the Caspian Sea (1997 - 2000) - Moghim, Mehdi; Fazli, H.; Ghaninejad, D.; Tavakcoly, M.; Behroz Khoshghalb, M.R.; Aghily, K.; Fadai, B.; Parafkandeh, F. (Iranian Fisheries Science Research Institute, 2002)
The present research experiment was conducted to evaluate the Sturgeons Stocks in the southern part of the Caspian See (Iranian side) by measuring different population parameters such as CPUE, length, age, weight, sex, caviar weight the biological sampling was collected from 9 commercial lending centers that were selected by clustering analysis. The total catch was estimated from the linear regression between flesh weight to total weight, catch per unite of effort was estimated expressed in kg/day/100 Panels of gillnet, In the past 10 years the changes in the sex combination and the average of length, weight, sex and the caviar rate of different species were discussed. The result indicated the remarkable decrease in the stocks of Stellate (Acipenser stellatus), Russian (Acipenser gueldenstaedtii, spiny sturgeon (Acipenser nudiventris, and Beluga sturcon (Huso huso). and despite of increasing the stocks of Persian sturgeon (Acipenser persicus). The species composition of Catch were effected remarkably by human activities, increasing the production and releasing the fingerlings, decreasing the natural production during the last 3() years. At the present, Persian sturgeon has the max catch rate in Iranian costal zones. Iranian Fisheries Science Research Institute Published